Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Siswa Kelas III Sekolah Dasar Negeri 03 Pontianak Kota - Firna Loka; Kartono; Rio Pranata; Muhammad Irfan Izudin; Nany Safrianty; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pengajaran, 2026)
The low mathematical problem-solving ability of elementary school students and the fact that mathematics instruction has not fully connected mathematical concepts with real-life contexts are the main problems addressed in this study. In addition, learning about length and weight measurement tends to be procedural, resulting in limited opportunities for students to develop deeper thinking skills. This study aims to analyze the effect of implementing Realistic Mathematics Education (RME) materials on length and weight measurement toward the problem-solving abilities of third-grade elementary school students. This research employed an experimental method using a quasi-experimental design in the form of a nonequivalent control group design. The subjects of the study were third-grade elementary school students divided into an experimental class and a control class. Data were collected using a measurement technique with essay test instruments. The data analysis methods included descriptive and inferential analyses through mean difference tests and effect size calculations. The results showed that the problem-solving abilities of students in the experimental class were categorized as better than those in the control class. Hypothesis testing indicated a significant difference between the two groups. The effect size analysis demonstrated that the implementation of Realistic Mathematics Education materials had a significant influence on students’ problem-solving abilities. The implications of this study indicate that the Realistic Mathematics Education approach is effective in improving elementary school students’ problem-solving abilities, particularly in the topic of length and weight measurement, and therefore can be used as an alternative mathematics learning strategy in elementary schools.